2014
DOI: 10.1155/2014/194967
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned Medium Reconditions Hippocampal Neurons against Kainic Acid Induced Excitotoxicity: AnIn VitroStudy

Abstract: Stem cell therapy is gaining attention as a promising treatment option for neurodegenerative diseases. The functional efficacy of grafted cells is a matter of debate and the recent consensus is that the cellular and functional recoveries might be due to “by-stander” effects of grafted cells. In the present study, we investigated the neuroprotective effect of conditioned medium (CM) derived from human embryonic kidney (HEK) cells in a kainic acid (KA) induced hippocampal degeneration model system in in vitro co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…BDNF and its receptors have been implicated in the development of epilepsy. Conditioned media can protect hippocampal neurons against KA-induced excitotoxicity, stimulating endogenous cell survival factors BDNF and anti-apoptotic Bcl-2 in the host cell ( 19 ). In addition, increased seizure activity has been found to upregulate BDNF mRNA and protein expression in immunoreactivity, and to activate TrkB in the epileptic brain ( 22 , 28 , 36 , 65 , 66 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…BDNF and its receptors have been implicated in the development of epilepsy. Conditioned media can protect hippocampal neurons against KA-induced excitotoxicity, stimulating endogenous cell survival factors BDNF and anti-apoptotic Bcl-2 in the host cell ( 19 ). In addition, increased seizure activity has been found to upregulate BDNF mRNA and protein expression in immunoreactivity, and to activate TrkB in the epileptic brain ( 22 , 28 , 36 , 65 , 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that epileptogenesis can be caused by changes in homeostatic mechanisms involving calcium ( 18 ). Overloading of glutamate receptor activation by KA receptors induces an influx of cellular Ca 2+ , production of reactive oxygen species (ROS) and mitochondrial dysfunction ( 19 , 20 ). Subsequently, Ca 2+ sequestration mechanisms cause neuronal insult and neuronal death, including, hypoxia, ischemia, and epileptic seizures ( 14 , 18 , 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secretome in a paracrine mechanism can significantly repair the tissues while the differentiation of cells has a minor benefit [ 5 ]. The secretome in conditioned medium may also stimulate the host's endogenous cell survival mechanism [ 6 ]. The majority of the studies reported that the beneficial effect is most likely mediated by modulation of neurotrophic factor expression [ 7 ].…”
Section: Introductionmentioning
confidence: 99%